MPEG digital video-coding standards - Sikora, T. (IEEE signal processing magazine, 1997)
The efficient digital representation of image and video signals has been the subject of considerable research over the past 20 years. Digital video-coding technology has developed into a mature field and products have been developed that are targeted for a wide range of emerging applications, such as video on demand, digital TV/HDTV broadcasting, and multimedia image/video database services. With the increased commercial interest in video communications, the need for international image- and video-compression standards arose. To meet this need, the Moving Picture Experts Group (MPEG) was formed to develop coding standards. MPEG-1 and MPEG-2 video-coding standards have attracted much attention worldwide, with an increasing number of very large scale integration (VLSI) and software implementations of these standards becoming commercially available. MPEG-4, the most recent MPEG standard that is still under development, is targeted for future content-based multimedia applications. We provide an overview of the MPEG video-coding algorithms and standards and their role in video communications. We review the basic concepts and techniques that are relevant in the context of the MPEG video-compression standards and outline MPEG-1 and MPEG-2 video-coding algorithms. The specific properties of the standards related to their applications are presented, and the basic elements of the forthcoming MPEG-4 standard are also described. We also discuss the performance of the standards and their success in the market place.